2014
DOI: 10.1021/es404842g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NOxon the Volatility of Secondary Organic Aerosol from Isoprene Photooxidation

Abstract: The effects of NOx on the volatility of the secondary organic aerosol (SOA) formed from isoprene photooxidation are investigated in environmental chamber experiments. Two types of experiments are performed. In HO2-dominant experiments, organic peroxy radicals (RO2) primarily react with HO2. In mixed experiments, RO2 reacts through multiple pathways, including with NO, NO2, and HO2. The volatility and oxidation state of isoprene SOA are sensitive to and exhibit a nonlinear dependence on NOx levels. Depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
169
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(181 citation statements)
references
References 103 publications
10
169
1
1
Order By: Relevance
“…Furthermore, isoprene SOA generated from different pathways (i.e., photooxidation under different RO 2 fates and reactive uptake of IEPOX; Surratt et al, 2010;Xu et al, 2014; produced similar responses for each inflammatory endpoint. These results suggest that different isoprene SOA products Xu et al, 2014; may induce similarly low inflammatory responses and are consistent with the intrinsic OP WS-DTT obtained for these SOA samples, where isoprene SOA generated the lowest OP WS-DTT of all SOA systems studied and the OP WS-DTT was similar for all SOA formation conditions explored (Tuet et al, 2017). This finding is in contrast to a previous study by Lin et al (2016), where methacrylic acid epoxide (MAE)-derived SOA was found to be substantially more potent than IEPOX-derived SOA.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, isoprene SOA generated from different pathways (i.e., photooxidation under different RO 2 fates and reactive uptake of IEPOX; Surratt et al, 2010;Xu et al, 2014; produced similar responses for each inflammatory endpoint. These results suggest that different isoprene SOA products Xu et al, 2014; may induce similarly low inflammatory responses and are consistent with the intrinsic OP WS-DTT obtained for these SOA samples, where isoprene SOA generated the lowest OP WS-DTT of all SOA systems studied and the OP WS-DTT was similar for all SOA formation conditions explored (Tuet et al, 2017). This finding is in contrast to a previous study by Lin et al (2016), where methacrylic acid epoxide (MAE)-derived SOA was found to be substantially more potent than IEPOX-derived SOA.…”
Section: Discussionmentioning
confidence: 91%
“…Alkenes substituted with an electron-withdrawing group (e.g., conjugated carbonyls) are commonly found in ring-opening products from the photooxidation of aromatic HCs (e.g., toluene; Jang and Kamens, 2001;Saunders et al, 2003Saunders et al, , 1997Wyche et al, 2009). The contributions of all three groups of SOA products to DTT activity can be influenced by the type of precursor HC (aromatics vs. biogenics) and by NO x (NO + NO 2 ) levels (HC / NO x ratios; Eddingsaas et al, 2012b;Jang and Kamens, 2001;Wyche et al, 2009;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, high concentrations of these undesirable contaminants in air pose serious health threats to human beings. In particular, these pollutants highly contribute to the formation of secondary organic aerosols (SOAs), which exert an impact on the climate as well [1,2]. The adverse effects on environmental and health have catalyzed research and development on the control of SOx and NOx.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, various methods and technologies have been put forward to curtail the emission of these pollutants. The technologies, such as wet flue gas desulfurization (WFGD) combined with selective catalytic reduction (SCR), or/and with selective noncatalytic reduction (SNCR), have been applied to remove NOx and SO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation